2015
DOI: 10.1016/j.jped.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Health promoting behaviors in adolescence: validation of the Portuguese version of the Adolescent Lifestyle Profile

Abstract: The ALP Portuguese version is a psychometrically reliable, valid, and useful measurement instrument for assessing health-promoting lifestyles in adolescence. The ALP is cross-culturally validated and can decisively contribute to a better understanding of adolescent health promotion needs. Additional research is needed to evaluate the instrument's predictive validity, as well as its clinical relevance for practice and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 15 publications
(14 reference statements)
3
26
0
1
Order By: Relevance
“…In addition, in sharing the experiences and difficulties of the other cultural adaptations already made with the DAS-24 in Taiwan 45 and Portugal 42 we could have an extended view of the interpretations of each observable variable (item). The inclusion of the original author of the instrument in the cross-cultural adaptation process had already been tested 46 and it was considered a positive procedural aspect in this process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in sharing the experiences and difficulties of the other cultural adaptations already made with the DAS-24 in Taiwan 45 and Portugal 42 we could have an extended view of the interpretations of each observable variable (item). The inclusion of the original author of the instrument in the cross-cultural adaptation process had already been tested 46 and it was considered a positive procedural aspect in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Sousa et al (23) found satisfactory values of internal consistency for the positive life perspective and health responsibility aspects. In this study, we found good values of internal consistency: a = 0.76 for health responsibility and a = 0.74 for positive life perspective.…”
Section: Methodsmentioning
confidence: 98%
“…Adolescents completed the Adherence to Weight Control Questionnaire (AWCQ) (21), the Impact of Weight on Quality of Life-Lite (IWQL-Lite) (22) and the Adolescent Lifestyle Profile (ALP-R2) (23).…”
Section: Methodsmentioning
confidence: 99%
“…This instrument was designed to measure the frequency of health-promoting behaviors in adolescents (early, middle, and late). The Portuguese version of ALP was validated by Sousa et al (2013c), from the original version of Hendricks et al (2006). The Portuguese version is a 36-item summated behavior rating scale that employs a four-point Likert-type response format, organized into seven factors (Health Responsibility, Physical Activity, Nutrition, Positive Life Perspective, Interpersonal Relationship, Stress Management, and Spiritual Health).…”
Section: Methodsmentioning
confidence: 99%